Pemberdayaan Ekonomi Umat Berbasis ‎Masjid ‎(Pengalaman BMT Masjid Nurul Jannah ‎Petrokimia Gresik)‎ - Abd Basid (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2009)
This article explores the concept of muslim community empowerment through Baitul Mal wat-Tamwil (BMT) or community treasury. The potentials of this economy institution is often undermined, even by muslims. BMT is considered out of dtae to tackle nowadays community’s economic challenges. The profile and business of BMT Nurul Jannah is uncovered to illustrate muslim community empowerment in Gresik. It turns out that the BMT which was established by the Nurul Jannah mosque foundation is designed to increase the role of the mosque in improving economic empowerment of the surrounding muslim community. BMT has two functions; it collects and distributes zakat (alms). In adition, it also channels credits for economic activities of muslim community in its surrounding.